2021
DOI: 10.1128/jcm.00543-21
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of BioFire FilmArray BCID2 for Blood Culture Processing in Clinical Practice

Abstract: Rapid pathogen characterization from positive blood cultures (BC) can improve management of patients with blood stream infections (BSI). The FilmArray blood culture identification (BCID) assay is a molecular test approved for direct identification of BSI causing pathogens from positive BC. A recently updated version of the panel (BCID2) comprises improved species identification characteristics, and allows for the detection of one ESBL- and several carbapenemase-encoding genes. Here, the clinical performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 28 publications
3
55
1
2
Order By: Relevance
“…Agreement between BCID2 and traditional culture methods was high in our study, with an overall concordance for on-panel pathogens on monomicrobial blood cultures of 98%, in line with existing reports [10,11,13,16,17]. This is a promising concordance rate, although it should be acknowledged that not all BCID2 targets were detected in our samples, therefore their performance could not be evaluated.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Agreement between BCID2 and traditional culture methods was high in our study, with an overall concordance for on-panel pathogens on monomicrobial blood cultures of 98%, in line with existing reports [10,11,13,16,17]. This is a promising concordance rate, although it should be acknowledged that not all BCID2 targets were detected in our samples, therefore their performance could not be evaluated.…”
Section: Discussionsupporting
confidence: 84%
“…Concordance between conventional testing and BCID2 for polymicrobial blood cultures is reported to be lower than that for monomicrobial blood cultures by some of the available performance studies [10,11]. Specifically, Berinson et al reported a concordance rate for polymicrobial samples of 61.3% [10] while Sparks et al of 28.6%, although in the latter study most disagreement was due to the culture-based identification of BCID2 off-panel pathogens, and possibly affected by a laboratory contamination [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are several commercially available, FDA-cleared blood culture identification (BCID) systems that use molecular methods for rapid identification of pathogens and antibiotic resistance genes (ARGs) in positive blood culture (PBC) bottles. One such system offers a single panel to detect 43 Gram-positive (GP) and Gram-negative (GN) bacteria and yeasts as well as 10 antibiotic resistance markers ( 5 7 ). Two other platforms offer separate panels for the identification of GP and GN bacteria, but neither has a fungal panel ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The FilmArray Blood Culture Identification panel detects 33 pathogen and 10 antimicrobial resistance genes associated with bloodstream infections [56]. For patients with sepsis, a leading cause of death in hospital patients, rapid identification of the organism from blood cultures in combination with the indication of pathogen-associated resistance genes is critical for reducing patient morbidity and mortality [57]. In addition, according to international guidelines for the management of sepsis, in order to reduce the occurrence of antimicrobial resistance, it is important to replace broad-spectrum therapy with appropriate antibiotic therapy as soon as pathogens are identified [58].…”
Section: The Biofire Filmarray Panelsmentioning
confidence: 99%